Investigation on micro region deformation of residual indents during temperature recovery - Xianke Li; Shunbo Wang; Guan Wang; Jiajian Meng; Zerui zhao; Hongwei Zhao (Journal of Materials Research and Technology, 2024)
Observation of residual indent is widely adopted to evaluate the mechanical properties of material in temperature indentation test. However, the potential influence of the difference between the testing and observing temperatures on the material is always neglected. In this study, crystal plasticity finite element model of copper was constructed, and the processes of high-temperature indentation test and specimen temperature reduction to the observed temperature after the test were simulated. The simulations showed that the error of test hardness can reach up to 4.92% as the residual indent area decreases with temperature decreasing from 800 °C to 20 °C. The stress values of the indentation influence zone were also reduced considerably, in which the maximum stress at 20 °C was 59% of that at 800 °C. The distribution of stresses at surface and subsurface both changed substantially, while the depth of the influence zone increased by 31%. The mechanical properties of material were also found to affect the micro region deformation of residual indents during temperature recovery. Therefore, the influence of temperature variation between the testing and observing processes on residual indent should be seriously considered.